PENERAPAN PRINSIP “GOOD FAITH” DALAM PERKARA SEWA MENYEWA GUDANG ANTARA WARGA NEGARA INDONESIA DENGAN WARGA NEGARA ASING (STUDI KASUS PUTUSAN MAHKAMAH AGUNG RI NO. 60 K/ PDT/2013) - FITRI HANDAYANI SINAGA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Muhd Yamin, SH, MS, CN2.  Dr. T. Keizerina Devi A, SH, CN, MHum3.  Dr. Syafril Sofyan, SH, MKn Leasing is a contract between two parties which is usually called bilateral agreemet. It causes right and obligation between them. This research analyzed a leasing contract of a building with its office equipment between the Indonesian citizen who was the lessor and a foreiger as the lessee or tenant. The research used juridical normative method by analyzing prevailing legal provisions such as contract law and the Civil Code. Its nature was descriptive analytic which gve argumentation of the result of the research. The result of the research shows that in a leasing contract of building the lessee is required to maintain, to take care of, and to keep the building he is renting ss if it were his.. The Panel of Judges' legal consideration of the Supreme Court's Ruling No. 2542.K/Pdt/2016 in the case of dispute in leasing a building is that the damage of the rented building owned by I Nyoman Yudhiawan is caused by the lessee's default in carrying out the clauses in the leasing contract, especially about the clause which states that a lessee should act as the owner of the owner of the house as it is stipulated in Article 1564 of the Civil Code in which the lessee is required to take the responsibility for all the damages in the materials he is renting during the leasing period unless hecan give evidence that all the damages have not heed done by him.Keywords: Good Faith, Leasing, Default